REGIONAL STUDIES OF THE BOOK CULTURE IN LITHUANIA - PETREIKIS, TOMAS (Knygotyra, 2013)
Regional studies are not ends in themselves; they have a clear methodological basis – regionalism – promoting the complex look at these studies, as well as the search for distinctive forms of regional cultural expressions. In Lithuania, century-long regional studies of book culture have survived an uneven evolution. It was influenced by the instability of the evolution of regionalism, the processes of sovietisation, and the inaction of current regional policy in the country. In the context of Eastern Europe, regional studies have not significantly lagged behind the general development of book science; thus, the attention to them has always remained fairly consistent. The largest historical gains are achieved by the studies of Lithuania Minor, started in the 20th century by Prof. V. Gaigalaitis and A. Bruožis, and in the 70s taken over and qualitatively developed by Prof. D. Kaunas. The most important historiographical achievement is the assessment of an autonomous concept of book culture in Lithuania Minor. It has been achieved by a consistent and systematic investigation of the press, publishing, library and book trade history in this region. Regional studies of the biggest regions of Lithuania – Aukštaitija, Dzūkija, Suvalkija, and Samogitia – differ significantly among themselves. Prof. V. Biržiška, who was the first to formulate the concept of the book of Samogitia, had given a positive shift in developing the further studies of this region. Despite the lack in generalising works, localized studies, as well as the analysis of individual issues facilitate the favourable conditions for the reconstruction of a multi-faceted picture of book culture in Samogitia. The maturity of studies in the regions of Aukštaitija, Dzūkija, Suvalkija, and Samogitia is considerably more modest – library studies are mainly developed, a smaller extent of book distribution is noticed. Therefore, a more broadly developed analysis of individual questions cannot represent the direction of regional studies. In general, regional studies lack social sections; consequently, the relationships of the inhabitants of different regions to the book are still difficult to imagine. From the institutional point of view, there is a lack of the concentration of regional study centres; as a result, the history research centres operating either in Klaipėda or in Šiauliai pay little attention to the problems of regional book history, and the researchers engaged in this activity do not always manage to overstep the boundaries of Šiauliai and Klaipėda cities. Since the middle of the 20th century, the most famous centre of the concentration of book science studies has been the one established in the Vilnius University; for this reason, representatives of library science and book studies in the regional studies accumulated the majority of theoretical and empirical knowledge. The historical past of the regions of Lithuania has a direct link to the maturity of regional studies, but the studies of book culture are not only historical. The fixation of the present situation and its analysis are of no less importance than the studies of the problems of the past book history. In the theoretical context of regional studies, we still lag behind our Eastern and Western neighbours; for this reason, we often solve contemporaneous historiographical problems rather than trying to find the continuity of the forms of regional book culture. From the positions of the book culture paradigm of V. Vasiliev, the majority of the aspects of book culture have been more or less explored, except for the problems of book art. The challenge for future studies is the search for theoretical and methodological decisions allowing the evaluation of regional book culture as a form of regional cultural expression.
Keywords: ...